2022
DOI: 10.3390/diabetology3010005
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress and Perspectives on Non-Invasive Glucose Sensors

Abstract: Self-monitoring of blood glucose forms an important part of the management of diabetes and the prevention of hyperglycaemia and hypoglycaemia. Current glucose monitoring methods either use needle-prick enzymatic glucose-meters or subcutaneous continuous glucose sensors (CGM) and thus, non-invasive glucose measurements could greatly improve the self-management of diabetes. A wide range of non-invasive sensing techniques have been reported, though achieving a level of precision comparable to invasive meters rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 92 publications
(103 reference statements)
3
17
0
Order By: Relevance
“…From Figure 4I, it can be found that the timeresolved PA signals of blood glucose shift towards right with the increase of detection distance, which is the same as the ultrasonic theory, that is, for the same specimens, the propagation time of ultrasonic wave is positively proportional to the detection distance. At the same time, from Figure 4J, the PA PPVs decreases with the increase of detection distance, which is also the same as the PA theory given in Equation (1), that is, the PA intensity is negatively proportional to the detection distance (r). Then, the PA detection experiments of blood glucose under the combination influence of five factors.…”
Section: Results and Analysessupporting
confidence: 75%
See 4 more Smart Citations
“…From Figure 4I, it can be found that the timeresolved PA signals of blood glucose shift towards right with the increase of detection distance, which is the same as the ultrasonic theory, that is, for the same specimens, the propagation time of ultrasonic wave is positively proportional to the detection distance. At the same time, from Figure 4J, the PA PPVs decreases with the increase of detection distance, which is also the same as the PA theory given in Equation (1), that is, the PA intensity is negatively proportional to the detection distance (r). Then, the PA detection experiments of blood glucose under the combination influence of five factors.…”
Section: Results and Analysessupporting
confidence: 75%
“…The PA amplitude of blood glucose increases with the laser energy. The PA PPVs of blood glucose linearly increase with the laser energies, which is identical to the PA theory given in Equation (1), that is, the PA intensity is positively proportional to the irradiation energy. In Figure 4C,D, the time-resolved PA signals and PPVs for different concentrations of blood glucose were obtained.…”
Section: Results and Analysessupporting
confidence: 61%
See 3 more Smart Citations